2009
DOI: 10.1038/ng.509
|View full text |Cite
|
Sign up to set email alerts
|

Scapuloperoneal spinal muscular atrophy and CMT2C are allelic disorders caused by alterations in TRPV4

Abstract: Scapuloperoneal spinal muscular atrophy (SPSMA) and hereditary motor and sensory neuropathy type IIC (HMSN IIC, also known as HMSN2C or Charcot-Marie-Tooth disease type 2C (CMT2C)) are phenotypically heterogeneous disorders involving topographically distinct nerves and muscles. We originally described a large New England family of French-Canadian origin with SPSMA and an American family of English and Scottish descent with CMT2C1,2. We mapped SPSMA and CMT2C risk loci to 12q24.1–q24.31 with an overlapping regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
206
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 232 publications
(224 citation statements)
references
References 31 publications
(46 reference statements)
13
206
0
1
Order By: Relevance
“…We then examined the binding of the R232C, R269H, R315W and R316H mutants, identified in CMT2C and other diseases [7][8][9]25 . All of these mutants, except for R232C, showed significantly decreased binding to PI(4,5)P 2 -containing liposomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We then examined the binding of the R232C, R269H, R315W and R316H mutants, identified in CMT2C and other diseases [7][8][9]25 . All of these mutants, except for R232C, showed significantly decreased binding to PI(4,5)P 2 -containing liposomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cells were maintained at À 30 mV, and the currents were elicited by slow voltage ramps (from À 100 mV to þ 100 mV, 0.6 s duration). The standard extracellular (bath) solution contained 100 mM NaCl, 6 mM KCl, 2 mM MgCl 2 , 1.5 mM CaCl 2 , 10 mM glucose and 10 mM HEPES (pH 7.38 adjusted with NaOH, and osmolality adjusted to 300 mmol kg À 1 with sucrose) 7 . The standard intracellular (pipette) solution contained 140 mM CsCl, 2 mM MgCl 2 , 10 mM EGTA, 2 mM Na 2 ATP, 0.1 mM NaGTP and 10 mM HEPES (pH 7.28 adjusted with CsOH, and osmolality adjusted to 298 mmol kg À 1 with sucrose) 7 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the human TRPV4 gene have been identified as the direct cause of divergent hereditary diseases, including skeletal dysplasias, spinal muscular atrophy, and CharcotMarie-Tooth disease type 2C (36)(37)(38)(39)(40)(41). Although the exact role of TRPV4 in the etiology of these clinically diverse diseases is unknown, it appears that many disease-causing mutations lead to gain of TRPV4 function (41).…”
Section: Discussionmentioning
confidence: 99%
“…In our original study, we tested two mutations, R316C and R269H, which were identified in the original SPSMA and CMT2C families, respectively (6). We found that in HEK293 cells, mutant TRPV4 had a physiological localization on the plasma membrane similar to wild-type TRPV4 (wtTRPV4).…”
mentioning
confidence: 99%